Elana Rôya - Karṇika, Dvā. Bha. (Dvārakānātha Bhagavanta), 1912- (Śrīvidyā Prakāśana, 1983)
Biography of Ellen Roy, 1904-1960, wife of Manabendra Nath Roy, 1893-1954, leader of the radical humanist movement.